The impact of social networks on the behavior of households’ participation in rural environmental human settlement improvement: evidence from Jiangxi Province, China - Chen, Chao; Peng, Ruohan; Ye, Feng; Liu, Yang (Frontiers in Psychology, 2025)
Promoting rural human settlement improvement and improving the quality of rural livability is an important part of enhancing farmers’ well-being. Based on the survey data of 512 farm households in Jiangxi Province, this study uses the multivariate ordered probit model and the mediation effect model to reveal the influence of social networks on the behavior of households’ participation in rural human settlement improvement and the mechanism of influence. The results show that the social networks can significantly mobilize households’ enthusiasm to participate in rural human settlement improvement, and the promotion effect of cadre-mass relationships in the social network is more evident than in neighborhood relationships. Social networks are more effective in promoting rural residents’ participation in environmental remediation among males, better-off families and non-plain areas. Ecological cognition and place attachment partially mediate the social networks to promote households’ participation in rural habitat improvement. Consequently, the government should encourage rural households to participate in environmental improvement by strengthening the construction of their social networks, improving their ecological knowledge, cultivating their place attachments and increasing the publicity of environmental improvement.